Old Romance place names in early South Slavic and late Proto-Slavic sound changes - Šekli, Matej (Linguistica (Ljubljana), 2015)
The analysis of Old Romance geographical names in early South Slavic confirms that the majority of late Proto-Slavic sound changes were still operative in the period of the earliest Old Romance-Slavic language contacts in the Balkan Peninsula and eastern Alps from the second half of the 6th century and the beginning of the 7th century onwards (...)
Keywords: changements phonétiques; fonetika; geografska imena; glasovne spremembe; južna slovanščina; langues romanes; langues slaves; phonetics; phonétique; praslovanščina; proto-roman; proto-slave; Proto-Slavic; romanski jeziki; slave méridional; Slavic languages; slovanski jeziki; stara romanščina; toponymes